Translation regulation of mRNAs by the fragile X family of proteins through the miRNA pathway - Cheever, Anne (RNA Biol, 2009)
Small, genomically-encoded microRNAs are important factors in the regulation of mRNA translation. Although their biogenesis is relatively well-defined, it is still unclear how they are recruited to their mRNA targets. The fragile X mental retardation protein family members, FMRP, FXR1P and FXR2P are RNA binding proteins that regulate translation of their cargo mRNAs. All three proteins, in addition to the single Drosophila ortholog, dFmrp, associate physically and functionally with the microRNA pathway. In this review, we summarize what is known about the role of the fragile X family members in translation regulation and highlight evidence for their association with the microRNA pathway. In addition, we present a new model for the role of phosphorylation on FMRP function, where phosphorylation of FMRP inhibits Dicer binding, leading to the accumulation of precursor microRNAs and possibly a paucity of activating microRNAs.